2022
DOI: 10.3390/en15134845
|View full text |Cite
|
Sign up to set email alerts
|

Application of Hydro Borehole Mining (HBM) Technology for Lignite Extraction—An Environmental Assessment (LCA) and a Comparative Study with the Opencast Method

Abstract: The article presents the impact of lignite mining on the environment associated with the introduction of hydro borehole mining (HBM) technology. The results are partially based on the HydroCoal Plus project results, where an environmental assessment of lignite HBM technology was performed. In order to reach the goals of the task, a life cycle assessment (LCA) study was used to assess selected environmental aspects of the HBM single-borehole lignite production process covering selected environmental impact cate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…The studies of cutting rocks using a high velocity jet of water (i.e. water jet) date from the 1960s 4 – 7 , when the mechanism and threshold conditions required to break rocks were investigated. It was found that a water jet with insufficient velocity would not be able to cut rocks but merely wash away the poorly cemented grains from the rock surface 8 , 9 .…”
Section: Introductionmentioning
confidence: 99%
“…The studies of cutting rocks using a high velocity jet of water (i.e. water jet) date from the 1960s 4 – 7 , when the mechanism and threshold conditions required to break rocks were investigated. It was found that a water jet with insufficient velocity would not be able to cut rocks but merely wash away the poorly cemented grains from the rock surface 8 , 9 .…”
Section: Introductionmentioning
confidence: 99%